(untitled) (International Journal of Engineering and Computer Science, 2017)
The first and greatest casualty of fraud is faith. According to [7] just over two-thirds (68%) of fraud victims say they are less willing to have faith on others after their fraud experience and 63% are less willing to make future investments. As far as, people with criminal intentions are concerned, identity theft is a conventional idea. A con man in police uniform, not cause many victims to become suspicious and they will comply with whatever they are told. Similarly, phishing is a form of online identity theft that aims to steal sensitive information from users such as online banking passwords and credit card information. This paper focuses on the phishing attacks which includes study of different contributions of recent research on phishing detection and prevention techniques. In addition of that based on the review, a new model for detection and prevention of phishing attacks is given in this paper.